High Prevalence of Occult Hepatitis B Infection (OBI) and its Molecular Characteristics among Pregnant Women in Surabaya, Indonesia (Microbiology Indonesia, 2016)
Perinatal transmission is the predominant mode of hepatitis B virus (HBV) transmission in countries where HBV infection is endemic. Newborns of HBV infected mothers have a high risk (up to 90%) of chronicity through perinatal transmission. HBsAg serology screening has been recommended to pregnant women, to prevent perinatal HBV infection. However, at present HBV DNA can be detected in serum with negative HBsAg (OBI - occult hepatitis B infection). The aim of this study was to determine the prevalence of occult hepatitis B infection (OBI) in pregnant women in Surabaya, Indonesia and its virological characteristics. A total of 50 HBsAg-negative and anti-HBc-positive sera were tested for anti-HBs and HBeAg. HBV DNA was isolated from these samples, analyzed by polymerase chain reaction (PCR) and sequenced. HBV DNA was detected in 9 (18%) samples, based on part of the S gene sequence. HBV/B3-adw2 was found predominant in 7 (77.7%) samples, HBV/B9-ayw1 in 1 (11.1%) sample, and HBV/C7-adrq+ in 1 (11.1%) sample. Three samples had mutations (Q129H, T131N, M133S, T140I, T126I) in the ‘a’ determinant region, which may play a role in the undetectability of the virus by the common HBsAg detection kit. The prevalence of OBI in pregnant women from Surabaya is high, but still in line with the general population in Asia. Application of anti-HBc antibody or HBV DNA detection in screening would be very beneficial and prevent perinatal transmission from OBI pregnant women.